Kepuasan Pelanggan Terhadap Produk Toko H. MANTI menggunakan Konsep Sistem Pendukung Keputusan dengan Metode Smart - Perdana, Rika Widya; Meri, Rozi (LPPM UNIKA Santo Thomas Medan, 2023)
The purpose of this research was to see how high customer satisfaction was with the products offered by Toko H. Manti. The sample used for research data processing is badcover sales data on sales from September 2022 to September 2023. Decision support system data processing using the SMART (Simple Multi. Attribute Rating Technique) method. The data processed is bedcover data by comparing several bedcover products, namely, raline, illusion, my love, diva linen, california, and d'luxe kintakun bedcover. Through this method, data is processed through several stages, namely determining criteria and weight values, determining weight values, normalizing weight values, and determining utility values, as well as determining the final value. By carrying out these steps, the result was that the raline bedcover got the highest weighted score with a score of 99 and the becover that got the lowest score was the illusion bedcover with a score of 53.